Implementation of the Kurikulum Merdeka in Informatics lessons at SMPN 4 Ciawigebang - Ramadhan, Mochammad Syahrul (Hipkin Journal of Educational Research, 2025)
This study aims to describe the implementation of the Merdeka Curriculum in Informatics at SMPN 4 Ciawigebang, focusing on the challenges faced, opportunities available, and strategies applied to support more adaptive learning that is relevant to students' needs in the digital era. A case study approach with a qualitative descriptive method was used, involving data collection through in-depth interviews with the school principal and Informatics teachers, direct classroom observations, and relevant document analysis. The main findings of this study show that, despite limitations in facilities, including a limited number of computers and inadequate laboratory conditions, SMPN 4 Ciawigebang successfully overcame these challenges through adaptive strategies, such as the use of students' personal devices and differentiated learning. Student-centered and project-based learning proved effective in enhancing student engagement and creativity. This research contributes significantly to understanding the implementation of the Merdeka Curriculum at the junior high school level, particularly in Informatics, which emphasizes the development of digital skills. The practical implications of these findings underscore the need for adequate infrastructure and ongoing teacher training to support the implementation of the curriculum. Further research is recommended to explore the long-term impact of this curriculum implementation and the role of technology in learning in schools with limited facilities.   Abstrak Penelitian ini bertujuan untuk menggambarkan implementasi Kurikulum Merdeka dalam mata pelajaran Informatika di SMPN 4 Ciawigebang, dengan fokus pada tantangan yang dihadapi, peluang yang ada, serta strategi yang diterapkan untuk mendukung pembelajaran yang lebih adaptif dan relevan dengan kebutuhan murid di era digital. Pendekatan yang digunakan adalah studi kasus dengan metode deskriptif kualitatif, yang melibatkan pengumpulan data melalui wawancara mendalam dengan kepala sekolah dan guru Informatika, observasi langsung terhadap kegiatan pembelajaran, serta studi dokumentasi yang relevan. Temuan utama penelitian ini menunjukkan bahwa meskipun terdapat keterbatasan sarana dan prasarana, seperti jumlah komputer yang terbatas dan kondisi laboratorium yang kurang memadai, SMPN 4 Ciawigebang berhasil mengatasi hambatan-hambatan ini dengan strategi adaptif, seperti pemanfaatan perangkat pribadi murid dan pembelajaran diferensiasi. Pembelajaran yang berpusat pada murid dan berbasis proyek terbukti efektif dalam meningkatkan keterlibatan dan kreativitas murid. Penelitian ini memberikan kontribusi penting terhadap pemahaman implementasi Kurikulum Merdeka di tingkat SMP, khususnya dalam bidang Informatika, yang berfokus pada pengembangan keterampilan digital. Implikasi praktis dari temuan ini adalah perlunya penyediaan infrastruktur yang memadai dan pelatihan berkelanjutan bagi guru untuk mendukung penerapan kurikulum ini. Penelitian lebih lanjut disarankan untuk mengeksplorasi dampak jangka panjang implementasi kurikulum serta peran teknologi dalam pembelajaran di sekolah dengan fasilitas terbatas. Kata Kunci: Kurikulum Merdeka; pembelajaran berdiferensiasi; strategi adaptif; teknologi dalam pendidikan